Book value and share prices: The mediating effect of inflation in Nigeria - Soje, Benedict; Tanko, Udisifan Michael (Goodwood Publishing, 2024)
Purpose: This study examines the nexus between book value and the share price of listed firms in the Nigerian exchange group, considering inflation as a mediating variable. Research methodology: The study used book value per share, share prices, and inflation rate as the independent, dependent, and mediating variables, respectively. The study uses regression analysis and a structural equation model for the effect and mediating effect, respectively, to analyze data collected from a company’s financial statements and the capital market for 2011-2020. Findings: The regression and structural equation model results show that book value per share has a negative and insignificant effect on share price, and inflation has a mediating effect on the relationship between book value per share and share prices. Limitations: This study was limited to book value per share, share price, and inflation rate. The scope of this study was limited to listed firms in Nigeria from 2011 to 2020. Contribution: This study contributes to the understanding of how inflation rates influence the relationship between book value per share and share prices in financial markets. By exploring the mediating effect of the inflation rate, this study sheds light on how changes in purchasing power affect the valuation metrics of companies, providing valuable insights for investors, policymakers, and financial analysts in making informed decisions amidst varying economic conditions. Moreover, this study contributes to the body of knowledge because there are limited studies in this area.